Improving the Quality of Oocytes of Old and Productive Ages White Rats (Rattus norvegicus) Using Pregnant Mare Serum Gonadotrophin (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2019)
Abstract This study was conducted to improve the quality of oocytes in old-female rats by using pregnant mare serum gonadotrophin (PMSG). Female rats at productive age were used as a control.  The experimental rats were injected with 4 doses of PMSG i.e., 0, 2.5, 5.0, and 10 IU PMSG. After 2 weeks of acclimation to the experimantal condition, the experimental rats were injected with PGF2α at a dose of 25µg/g BW two times with 2 days interval to synchronize estrous cycle. PMSG injections were conducted at the same time with the second PGF2α injection.  After PMSG injection, the experimental rats were divided into two groups rats, i.e., rats without mating for masurement of oocyte qualities and rats mated for measurement of offspring qualities.  Therefore, 16 experimental rats from each age group were sacrifized for maeasurement of oocyte qualities.  The other 16 experimental rats for each age group were mated for measurement of offspring qualities. Parameters measured were hematological profile, uterine and ovarian weights, the qualities of oocytes, the qualities of the offsspring born by using swimming test and rat maze test. The collected data were analyzed by analysis of variance (ANOVA) and continued with Duncan test with a 95% confidence level. The data were analyzed using SSPS. The results showed that the improvement in the quality of oocytes in old female rats using the PMSG hormone in this study showed an increase in the quality of oocytes in old and productive age rats. The highest number of oocyte quality was found in rats of productive age (3.25) and significantly different (P< 0.05) from the other oocyte qualities. The quality of offspring born to old age and productive age rats injected with PMSG were improved.  It was concluded that the improvement of oocyte quality by using PMSG also improves offspring qualities.
Keywords: oocyte quality; offspring quality; PMSG hormone; old age; productive age